Electoral Threshold: Pros-Cons and Political Party Consensus in Indonesia - Amrurobbi, Azka Abdi; Daviska, Donis; Mahadika, Alam (Universitas Padjadjaran, 2026)
The debates surrounding the parliamentary threshold and presidential threshold have become a recurring phenomenon, particularly in the period leading up to general elections in Indonesia. This paper aims to examine the pros and cons of the implementation and determination processes of both thresholds. Employing a qualitative research method and library research as the primary data collection technique, to validate the data then this research used data triangulation technique. In the Indonesian context, the thresholds applied constitute a form of formal threshold, namely thresholds determined through political and legislative processes in parliament. Consequently, threshold policies are heavily influenced by the configuration of political power among parties. This study finds several key points: First, the discourse on the parliamentary and presidential thresholds has generated intense debate among political scholars, ranging from those who support to those who oppose it, each with their own rationales. Second, the application of formal thresholds as a political product is largely shaped by the position of political parties and the results of previous elections. Consequently, political parties’ responses to the thresholds are inherently dynamic and subject to change over time.